L-arginine minimizes immunosuppression and prothrombin time and enhances the genotoxicity of 5-fluorouracil in rats - de Andrade Bernal Fagiani, Marcela; Fluminhan, Antônio [UNESP]; de Azevedo Mello, Fabíola; Yabuki, Denise; Gonçalves, Gracielle Vieira; Tsujigushi, Leticia Kazama; Pereira, Liliane Girotto; da Silva, Kesia Araújo; da Silva, Sara Bertozo Bezerra; Santarem, Cecilia Laposy; Giozo, Paulo Felipe Izique; de Souza Reis, Luis Souza Lima (Elsevier, 2019)
Objective: The aim of this study was to evaluate the effect of low doses of L-arginine supplementation on hemogram, integrity of DNA and spleen, inflammatory infiltrate in the jejunum, and in the coagulogram of rats submitted to 5-fluorouracil (5-FU) chemotherapy. Methods: Thirty-two Wistar rats were fed commercial feed and water ad libitum and grouped into four (eight rats per group): The control group was given a 0.9% physiologic solution to simulate the application of 5-FU in the other groups; the G5-FU group was given a dose of 5-FU; the GArg50 and GArg100 groups were given a dose of 5-FU and supplemented with 50 and 100 mg L-arginine/d added in the drinking water ad libitum. Results: The rats in the GArg50 group did not lose weight after chemotherapy. GArg50 rats presented polycythemia owing to dehydration caused by diarrhea generated by 5-FU. GArg100 rats had increased total leukocyte count, eosinophils, lymphocytes, and index in the total index of DNA damage, yet showed a reduction in prothrombin time and in the spleen depletion index. Rats in the G5-FU, GArg50, and GArg100 groups had similar moderate inflammatory infiltrate in the jejunum. Conclusion: Supplementation with 100 mg/d of L-arginine minimized immunosuppression, spleen depletion, and prothrombin time and contributed to the breakdown of 5-FU–generated DNA in Wistar rats. Supplementation with 50 mg/d of L-arginine decreased the weight loss generated by 5-FU in Wistar rats. Supplements with 50 or 100 mg of L-arginine did not interfere with 5-FU–generated jejunal inflammatory infiltrate.
Keywords: arginine; cytotoxicity; drug therapy; immunologic; neoplasms